Analisa Pengaruh Peletakan Panel Surya di Atas Deck House Kapal Ikan 30 GT Terhadap Keselamatan Operasional Penangkapan Ikan - Shanty Manullang; Rizky Irvana; Ayom Buwono; Mercy Patanda (Universitas Sam Ratulangi, 2023)
The purpose of this study is to analyze the effect of laying solar panels on the deckhouse of small fishing vessels 30 GT. The additional load above which causes weight gain and will affect the ship's center of gravity is became the first effect of Fishing vessel stability. The second effect is on how the fishing vessel performs when there is a solar panel on the vessel. The data were collected by measuring the stability according to A.N Kyrylo’s method with standard checks according to the IMO (International Marine Organization). Code on Intact stability calculated the ship motion by using the STRIP method and measuring the wave characteristics using the JONSWAP method with the help of Maxsurf software. The results of this research show that the installment of solar panels above the deckhouse does not really affect the stability, where the results were agreed to the IMO standard criteria. Moreover, the success of the fishing operation will be more visible if the vessels operated on waves under 2 meters due to the more stable movement according to its seakeeping performance .